The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12966-022-01404-y
|View full text |Cite
|
Sign up to set email alerts
|

Active school commuting in adolescents from 28 countries across Africa, the Americas, and Asia: a temporal trends study

Abstract: Background Evidence examining trends in active school commuting among adolescents are mainly single-country studies, and principally focused on high-income countries. Thus, the present study aims to examine temporal trends in adolescents’ active school commuting and to examine if there are differences in such trends by sex. We used nationally representative samples of 28 countries, which were predominantly low- and middle-income countries (LMICs), covering 5 different WHO regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Recognizing the necessity for sustainable transportation solutions for students, research into the commuting behaviors of university students has been gaining interest, including both high-income countries (HICs) [3,[6][7][8][9]] and low-and middle-income countries (LMICs) [10][11][12][13]. A recent investigation involving 28 LMICs, which examined adolescent active travel to schools, identified considerable diversity and heterogeneity among the LMICs studied, highlighting the need for context-specific research within these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the necessity for sustainable transportation solutions for students, research into the commuting behaviors of university students has been gaining interest, including both high-income countries (HICs) [3,[6][7][8][9]] and low-and middle-income countries (LMICs) [10][11][12][13]. A recent investigation involving 28 LMICs, which examined adolescent active travel to schools, identified considerable diversity and heterogeneity among the LMICs studied, highlighting the need for context-specific research within these countries.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the mobility patterns of students commuting to universities are often not thoroughly studied. While there is some research on this topic for High-Income Countries (HICs) [3,[5][6][7][8] it remains under-researched for Low-and Middle-Income Countries (LMICs), with only a few studies identified [9,10]. The most recent research, which covered 28 LMICs, focused on adolescent active travel to schools but did not explore public transport or the barriers and factors affecting sustainable transport [10].…”
Section: Introductionmentioning
confidence: 99%
“…While there is some research on this topic for High-Income Countries (HICs) [3,[5][6][7][8] it remains under-researched for Low-and Middle-Income Countries (LMICs), with only a few studies identified [9,10]. The most recent research, which covered 28 LMICs, focused on adolescent active travel to schools but did not explore public transport or the barriers and factors affecting sustainable transport [10]. However, an interesting finding from this study is the high level of heterogeneity among LMICs, which underscores the need for context-specific research in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…[17]. Globally, among school-adolescents, mixed trends were found for food insecurity in 14 countries [18], sedentary behaviour had stable trends in most countries [19], regarding current alcohol use adolescent surveys showed more likely decreasing than increasing trends in study countries [20]. While there was signi cant variation in the trends of being bullied among the studied countries, six and thirteen countries, respectively, showed a signi cant increasing and decreasing trend [21], most countries had stable trends with high prevalence of loneliness over time [22].…”
Section: Introductionmentioning
confidence: 99%